Smart Home: Power Electric Monitoring and Control in Indonesia - Prasetyo, Novian Adi; Prabawati, Andhika Galuh; Suyoto, Suyoto (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The development of the Internet of Things Industry in Indonesia is increasing rapidly from year to year. One of the uses in this industry is being able to carry out monitoring, control, and analysis. The smart home is one of the applications of IoT that is used in households to make it easier for humans to monitor and control all devices at home. Most homes in Indonesia have various commonly used resources, these are water, electricity, and gas. These resources will run out quickly if humans cannot use them properly. Therefore we need to monitor and control the resources we have at home. One of the resources that will be monitored and controlled in this study is electricity resources because it is more widely used in every corner of the house and almost all household devices use these electricity resources. This research proposes a way to do electricity use effectiveness with monitoring and power control using cloud-based IoT. The proposal discussed in the paper is expected to have other benefits besides saving electricity resources, but it is also expected to reduce the cost of energy use at home.